The effects of idea rejection on creative self‐efficacy and idea generation: Intention to remain and perceived innovation importance as moderators. (8th October 2021) - Ng, Thomas W. H.; Shao, Yiduo; Koopmann, Jaclyn; Wang, Mo; Hsu, Dennis Y.; Yim, Frederick H. K.
Summary: In the pursuit of innovation, it is inevitable that many employee ideas will be disapproved of by supervisors, discouraging employees' idea generation. This idea rejection–idea generation link is important to examine because it extends current thinking which treats idea generation as the beginning stage of a creative process. Guided by social cognitive theory, this study proposes that the idea rejection–idea generation link is mediated by creative self‐efficacy. We further posit that whether idea acceptance is a salient goal is a meta‐level moderator. To capture this factor, we examine intention to remain and perceived innovation importance: Idea rejection should yield a stronger negative impact on creative self‐efficacy for those who intend to remain with the organization and perceive innovation as important to the organization, as stayers who understand the importance of innovation to their employers would view idea acceptance as a salient goal and thus react most strongly to idea rejection. Data collected from a field study and a scenario experiment supported most of our hypotheses. Thus, this study highlights idea rejection as a crucial variable, directs researchers' attention to the idea rejection–idea generation relationship, and underscores the variability in employee reactions to idea rejection.